The people we know: Social network diversity among urban Malaysians - Rycker, Antoon De; Yang, Nicole Yang Lai; Ramachandran, Ponnan; Lokasundari, V. S.; Lee, Cheng Ean Catherine * (USM Press, 2015)
Social networks are an important source for individual social actors to access critical resources (e.g., information and support) and can be variably associated with tolerance, social harmony and nation building, also under conditions of rapid urbanisation. The purpose of this paper is to provide much-needed factual and quantitative details regarding the social networks of urban Malaysians. The approach includes self-report questionnaire data obtained in the first half of 2014 from a representative sample of 808 respondents, aged 31 to 55, living in five major cities/towns across the Klang Valley, Malaysia. Findings show that urban Malaysians function within social networks that are racially, culturally and socio-economically heterogeneous, interacting with all major groups in Malaysian society, including neighbours. For the vast majority, however, the observed degree of network diversity is medium to low. The analysis also suggests that social network diversity is no indication of the closeness or importance accorded to the social relationships involved. A final finding is that social network diversity weakly correlates with respondents’ sex, race and religion but not with their age or employment status. Overall, this study seems to point to the existence, among urban Malaysians, of a dual social network system: a more closely knit homogeneous network based on family ties versus a looser and more heterogeneous network of non-family contacts. Among the non-family contacts, the observed diversity can be hypothesised to be a diversity of necessity rather than one by choice. Potential political and social implications will be discussed.